2017
DOI: 10.1177/1471301217737413
|View full text |Cite
|
Sign up to set email alerts
|

Decisions and attitudes regarding participation and proxy in clinical trials among patients with impaired cognitive function

Abstract: Background Medical decision-making capacity is impaired in Alzheimer's disease and mild cognitive impairment. Medical decision-making capacity depends on many different cognitive functions and varies due to situation and cognitive, social, and emotional status of the patient. Our aim was to analyze dementia patients' capacity to estimate risks and benefits in different clinical trials and determine how cognitive decline affects their attitude toward possible participation and proxy consent. Methods Groups: Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Deficits in memory and reasoning may affect medical DM differently as patients are required to recall the risks and benefits of each treatment option as well as to balance/compare them to justify the decision made [ 94 ]. While the aforementioned studies relied on the utilization of the Capacity to Consent Treatment Instrument (CCTI; [ 106 ]), other works adopted the Linguistic Instrument for Medical Decision-Making (LIMD) to measure the requirements for medical choices, finding altered responses in groups with different profiles of cognitive impairment [ 73 , 84 , 86 ]. Mental abilities covering clinical judgement appeared to be preserved in MCI despite lower DM scores for other areas of daily life, compared to those of cognitively spared individuals [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in memory and reasoning may affect medical DM differently as patients are required to recall the risks and benefits of each treatment option as well as to balance/compare them to justify the decision made [ 94 ]. While the aforementioned studies relied on the utilization of the Capacity to Consent Treatment Instrument (CCTI; [ 106 ]), other works adopted the Linguistic Instrument for Medical Decision-Making (LIMD) to measure the requirements for medical choices, finding altered responses in groups with different profiles of cognitive impairment [ 73 , 84 , 86 ]. Mental abilities covering clinical judgement appeared to be preserved in MCI despite lower DM scores for other areas of daily life, compared to those of cognitively spared individuals [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…One recent study investigated the decisions and attitudes concerning participation in clinical trials under different conditions of risks, highlighting differences only in the group with AD and non-MCI and healthy subjects [ 73 ], whereas previous research showed a progressive deterioration in these faculties becoming observable even in individuals with MCI [ 86 ]. Further evidence from factorial analyses revealed the critical role of verbal knowledge in predicting DM performances; in contrast, reading speed emerged as the most predictive measure deriving from the administration of a single test [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…A purposeful sampling method was chosen to capture experiences which could enhance the knowledge of the field (Polit & Beck, 2017). Thorne (2016) (Folstein et al, 1975) score ≥15p as described by Stormoen et al (2017) as a cutoff point for informed consent and ability to converse and communicate in Swedish or English.…”
Section: Me Thodmentioning
confidence: 99%
“…A recent study investigated the predictive ability of 27 cognitive tests in classifying capacity to consent to medical treatment using a vignette paradigm (Stormoen, Almkvist, Eriksdotter, Sundstr€ om, & Tallberg, 2014). Their sample included patients with Alzheimer's disease (AD), mild cognitive impairment (MCI) and healthy controls (HC).…”
Section: Consent To Research or Treatmentmentioning
confidence: 99%